Stochastic methods for estimation and problem-solving in engineering - Kadry, Seifedine 1977- (Advances in mechatronics and mechanical engineering (AMME) book series, 2018)
"This book explores stochastic methods and their applications. It examines current and future works, discuss proposed methods and solutions, and describe challenges and opportunities in this area. It explores the following issues as well: stochastic methods in different kind of engineering and stochastic methods in business and sciences"...